Defusing Master Narratives: Decolonial, Insurgent, Gentle Moves in a Con-Text of Teacher Education and Educational Research - Yedaide, Maria Marta (2020)
This article intends to share a very particular perspective on teacher education and educational research while asserting the inevitability, inescapability, of such local epistemological bias. It discusses the hermeneutic, narrative, decolonial and performative turns and their interplay with the geocultural and political conditions in a con-text which is acknowledged as highly productive (and strongly conditioning) of social meaning. On the basis of teaching and research experience, some insurgent, gentle moves have been designed as ethico-onto-epistemological gestures to experiment on concrete possibilities of fluidity and instability for master narratives. Far from naïvely believing in the “fall”, “end” or “breaking down” of these narratives, defusing them involves instead a positioning on language, narrative and discourse capable of devising provisional and changing patterns of contingent intelligibility which allow for greater exercise of civic sovereignty. Critical, decolonial and queer pedagogies actually constitute the core beliefs which—subjected to the constraints of contingency—are asked to perform this double role of both structuring and shattering grand narratives. It must be noted that this positioning has implied an explicit rejection of the use of passive voice and the (impersonalized) third person in writing this article. The choice of the pronoun “we” constitutes in itself a political gesture –an exercise of rhetoric prerogative, in the terms Segato (2019), Walsh (2011), and Yedaide (2017) propose—. In addition, we affiliate to the thesis which claims that separating the personal and the political constitutes a modern technology: a culture of the non-culture (Haraway, 1997), that is to say, a maneuver that conceals the necessary political bias present in all social products, even and especially when these are self-presented as merely technical. As to our use of English in writing—though apparently contradictory with the epistemic authority we defend—it must be read simply as a gesture manifesting willingness to engage in productive dialogue with peoples who do not speak Spanish. The choice of splitting the word “context” as “con-text” aims at raising awareness regarding the decisive influence that any setting exercises in meaning-making (a site should not be taken as merely ornamental or as landscape/ background but rather as an agent, productive in the construction of meaning, we argue.